Depreciation of the Franc in a French Colony - Southworth, Constant (Quarterly Journal of Economics, 1926)
Journal Article Depreciation of the Franc in a French Colony Get access Constant Southworth Constant Southworth Dakar, Senegal Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 40, Issue 3, May 1926, Pages 554–557, https://doi.org/10.2307/1885179 Published: 01 May 1926